Metabolism of glycerol in pigs fed diets containing mixed crude glycerin and β-adrenergic agonist - Pinto, Adriana Brasil Ferreira (2018)
Glycerol is an important component of animal metabolism that can be directed for triacylglycerols or glucose synthesis or be oxidized for energy production. Crude glycerin has a high concentration of glycerol (70 to 95%) and high energy (approximately 4.320 kcal gross energy / kg) and, therefore, has been studied as an energy source in the diet of farm animals , such as pigs. Ractopamine, in turn, has been used as a dietary supplement for pigs, in order to obtain carcasses with lower fat content and higher lean mass, improving the production process and making the meat of these animals more competitive in market. Thereby, the optimization of the use of mixed crude glycerin (MCG) and the ractopamine hydrochloride (RH) in diets for finishing pigs requires a better understanding of glycerol metabolism. Therefore, this study evaluated the performance of blood parameters, metabolite levels in the Longissimus lumborum muscle and the activity of enzymes in the liver, subcutaneous adipose tissue and kidney of pigs fed diets containing MCG and/or RH. According to the initial weight, 64 barrows were distributed in a 4 x 2 factorial design, corresponding to four concentration of MCG (0, 100, 150, and 200 g/kg) in diets containing 0 or 10 mg/kg RH. Each animal was considered an experimental unit, being used eight repetitions per treatment. The performance during the experimental period of 28 days was evaluated. At the end of the experiment, samples of blood, muscle Longissimus lumborum, liver, subcutaneous fat, and kidney were collected. There was no interaction between MCG x RH for all the evaluated parameters. Moreover, there was no isolated effect of dietary MCG or RH on the weight gain and the blood concentrations of glucose, insulin, triacylglycerols, total cholesterol, total protein, albumin, creatinine, cortisol, and lactate. However, regardless the supplementation of RH in the diet, the increase of MCG concentration in the diet affected the daily feed intake and the daily intake of MCG, increasing the level of glycerol kinase (GK) in the liver and the malic enzyme at the adipose tissue. On the other hand, regardless the dietetic concentration of MCG, the inclusion of RH in the diet improved food conversion rate, reduced the glycerol concentration in the muscle, decreased the GK activity and glycerol-3-phosphate dehydrogenase in the liver and glucose-6-phosphate dehydrogenase in adipose tissue, also increasing the activity of hepatic glutamate dehydrogenase. There was a higher rate of phosphorylation of glycerol in the liver, stimulation of lipogenesis in adipose tissue and a likely increase in the utilization of glycerol by muscle fibers in response to an increased concentration of circulating glycerol from the diet. On the other hand, when the diet contained up to 200 g/kg MCG and 10 mg/kg RH, there were indications of lower utilization of glycerol for the synthesis of triacylglycerols in muscle, liver and adipose tissue, besides increased oxidation of amino acids in the liver followed by improved feed conversion of pigs.